A Companion to the Byzantine Culture of War, circa 300-1204. - Yannis Stouraitis (Volume Editor)
1 online resource.
Keywords: This collection of essays on the Byzantine culture of war in the period between the 4th and the 12th centuries offers a new critical approach to the study of warfare as a fundamental aspect of East Roman society and culture in Late Antiquity and the Middle Ages. The book’s main goal is to provide a critical overview of current research as well as new insights into the role of military organization as a distinct form of social power in one of history’s more long-lived empires. The various chapters consider the political, ideological, practical, institutional and organizational aspects of Byzantine warfare and place it at the centre of the study of social and cultural history. Contributors are Salvatore Cosentino, Michael Grünbart, Savvas Kyriakidis, Tilemachos Lounghis, Christos Makrypoulias, Stamatina McGrath, Philip Rance, Paul Stephenson, Yannis Stouraitis, Denis Sullivan, and Georgios Theotokis.